Influence of Meteorological Parameters on Particle Pollution (PM2.5 and PM10) in the Tropical Climate of Port Harcourt, Nigeria - Christopher U. Onuorah; Tambari G. Leton; Yusuf O. L. Momoh (Archives of Current Research International, 2019)
Aims: This study explores the influence of meteorological parameters such as wind direction, wind speed, rainfall, air temperature and relative humidity on PM2.5 and PM10 concentration. Place and Duration of Study: The study was conducted in Woji, an urban area of Port Harcourt city in Nigeria, between May and December 2019 covering wet and dry season. Methodology: The PM10 and PM2.5 concentrations were monitored for 236 days using photometric laser based particulate monitor while meteorological parameters were collected using Misol weather station mounted 10m above ground at Woji monitoring location. Results: PM concentration for all the months under study were below USEPA 24-hr standard except the month of December with PM2.5 = 58.8 μg/m³ and PM10 = 164.5 μg/m³. The result showed a significant but positively strong correlation between PM2.5 and PM10 (r = 0.97, P < .001). The wind speed significantly influenced PM2.5 and PM10 concentration with a weak negative correlation (r = - 0.22 and -0.23) respectively at P < .001. Also, PM2.5 and PM10 concentration exhibited a weak negative but significant correlation with rainfall (r = - 0.05 and -0.05) and air temperature (r = - 0.12 and -0.14) respectively at P< .001. Relative humidity showed a weak negative but not significant correlation with PM2.5 concentration (r = - 0.01) while PM10 exhibited weak but significant correlation with relative humidity (r = 0.04). Conclusion: The PM concentration exceedances recorded in month of December could be attributed to dry dusty north east trade wind that comes with harmattan as well as high atmospheric stability which is associated with low wind speed. The study revealed that meteorological parameters such as temperature, wind speed and rainfall plays significant role in the reduction of particulate matter loading through air dispersion, atmospheric instability and washout process while relative humidity increases PM10 concentration.